Transcriptional analysis of Ceratopteris richardii young sporophyte reveals conservation of stem cell factors in the root apical meristem - Aragón-Raygoza, Alejandro; Herrera-Estrella, Luis; Cruz-Ramírez, Alfredo (Frontiers in Plant Science, 2022)
Gene expression in roots has been assessed in different plant species in studies ranging from complete organs to specific cell layers, and more recently at the single cell level. While certain genes or functional categories are expressed in the root of all or most plant species, lineage-specific genes have also been discovered. An increasing amount of transcriptomic data is available for angiosperms, while a limited amount of data is available for ferns, and few studies have focused on fern roots. Here, we present a de novo transcriptome assembly from three different parts of the Ceratopteris richardii young sporophyte. Differential gene expression analysis of the root tip transcriptional program showed an enrichment of functional categories related to histogenesis and cell division, indicating an active apical meristem. Analysis of a diverse set of orthologous genes revealed conserved expression in the root meristem, suggesting a preserved role for different developmental roles in this tissue, including stem cell maintenance. The reconstruction of evolutionary trajectories for ground tissue specification genes suggests a high degree of conservation in vascular plants, but not for genes involved in root cap development, showing that certain genes are absent in Ceratopteris or have intricate evolutionary paths difficult to track. Overall, our results suggest different processes of conservation and divergence of genes involved in root development.